Pembubaran Ormas Islam oleh Pemerintah; Studi Komparatif Undang-Undang Ormas dan Hukum Islam - Syahrul Mubarak; Azman Arsyad (Universitas Islam Negeri Alauddin Makassar, 2021)
The concept of mass organizations is discussed in the legal order in Indonesia. Ormas itself or community organization is an organization founded and formed by the community voluntarily based on common aspirations, desires, needs, interests, activities, and goals to participate in development in order to achieve the goals of the Republic of Indonesia based on Pancasila and the Constitution of the Republic of Indonesia. 1945. The mass organizations were then unilaterally disbanded by the government with reference to the Law on the dissolution of Social Organizations and Islamic Law concerning the dissolution of community organizations. The main problem of this paper is how the concept of Islamic mass organizations in the legal order in Indonesia, how the indications for the unilateral dissolution of mass organizations by the government and how to review positive law and Islamic law regarding mass organizations. Community organization is a forum formed by a group of people who have the same vision, mission, ideology, goals and have clear members. According to the author, in one of the main principles of fiqhiyyah which is very popular among Muslims, it says that